1998
DOI: 10.1046/j.1365-2915.1998.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal toxicity of Japanese Bacillus thuringiensis against the mosquito Anopheles stephensi

Abstract: Japanese isolates of Bacillus thuringiensis were screened for larvicidal activity against the mosquito Anopheles stephensi, the urban malaria vector of the Indian subcontinent. Among more than 30 strains identified, larvicidal activity causing > 80% mortality in 72 h was demonstrated for 41/1449 (2.8%) isolates. The majority of strains and isolates (97.2%) exhibited little or no larvicidal activity. Anopheles-active strains belonged to more than 12 H serotypes, especially H3ade (serovar fukuokaensis) and H44 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…The spore-inclusion mixture was harvested from sporulated cultures and the inclusions were partially purified by a biphasic separation method (6) using polyethylene glycol 6000 (Wako Pure Chemical, Osaka, Japan) and sodium dextran sulfate 500 (Sigma, St. Louis, Mo.). Inclusions were further purified by sucrose density gradient centrifugation as previously reported (25). The purified inclusions were stored at Ϫ20°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…The spore-inclusion mixture was harvested from sporulated cultures and the inclusions were partially purified by a biphasic separation method (6) using polyethylene glycol 6000 (Wako Pure Chemical, Osaka, Japan) and sodium dextran sulfate 500 (Sigma, St. Louis, Mo.). Inclusions were further purified by sucrose density gradient centrifugation as previously reported (25). The purified inclusions were stored at Ϫ20°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…It has been well established that: (i) B. thuringiensis H serotype £ora in Japan is highly heterogeneous, consisting of more than 40 H serogroups, and (ii) many of the H serogroups, detected in the present study, commonly occur in B. thuringiensis natural populations as well [18]. In addition, previous investigators have reported that B. thuringiensis accounts for 1^5% of the B. cereus/B.…”
Section: Discussionmentioning
confidence: 61%
“…Speci¢c antisera against H antigenic subfactors, existing in H serotypes 3,4,5,8,10,11,18,20,24, and 28 [9], were prepared by the saturation technique as described previously by de Barjac [15]. H serotyping was done with slide agglutination tests [14] by using young £agellated broth cultures (37 ‡C, 3^4 h) of B. cereus isolates.…”
Section: Identi¢cation Of H Antigen Serotypesmentioning
confidence: 99%
“…It is likely that low-levels of inclusion-forming cells (Ͻ1% of the cell populations), coupled with the low toxicity of inclusion proteins, may lead to a failure to detect insecticidal activity of the spore/ inclusion mixtures. Previous investigators have also reported that sporulated cultures of the existing yunnanensis strains gave no significant mortalities to other lepidopterans and dipterans tested (Wang et al, 1979;Ohba, 1996;Saitoh et al, 1996Saitoh et al, , 1998Mizuki et al, 1999a;Higuchi et al, 2000;Ohba et al, 2000Ohba et al, , 2002 and a coleopteran (Tsuchiya et al, 2002).…”
Section: Discussionmentioning
confidence: 99%